Avian Paramyxovirus Type 1 in Egypt: Epidemiology, Evolutionary Perspective, and Vaccine Approach - Mansour, Shimaa M. G.; ElBakrey, Reham M.; Mohamed, Fakry F.; Hamouda, Esraa E.; Abdallah, Mona S.; Elbestawy, Ahmed R.; Ismail, Mahmoud M.; Abdien, Hanan M. F.; Eid, Amal A. M. (Frontiers in Veterinary Science, 2021)
Avian orthoavulavirus 1, formerly known as avian paramyxovirus type-1 (APMV-1), infects more than 250 different species of birds. It causes a broad range of clinical diseases and results in devastating economic impact due to high morbidity and mortality in addition to trade restrictions. The ease of spread has allowed the virus to disseminate worldwide with subjective virulence, which depends on the virus strain and host species. The emergence of new virulent genotypes among global epizootics, including those from Egypt, illustrates the time-to-time genomic alterations that lead to simultaneous evolution of distinct APMV-1 genotypes at different geographic locations across the world. In Egypt, the Newcastle disease was firstly reported in 1947 and continued to occur, despite rigorous prophylactic vaccination, and remained a potential threat to commercial and backyard poultry production. Since 2005, many researchers have investigated the nature of APMV-1 in different outbreaks, as they found several APMV-1 genotypes circulating among various species. The unique intermingling of migratory, free-living, and domesticated birds besides the availability of frequently mobile wild birds in Egypt may facilitate the evolution power of APMV-1 in Egypt. Pigeons and waterfowls are of interest due to their inclusion in Egyptian poultry industry and their ability to spread the infection to other birds either by presence of different genotypes (as in pigeons) or by harboring a clinically silent disease (as in waterfowl). This review details i) the genetic and pathobiologic features of APMV-1 infections in Egypt, ii) the epidemiologic and evolutionary events in different avian species, and iii) the vaccine applications and challenges in Egypt.